2017
DOI: 10.1186/s12864-017-4117-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolving DNA methylation and gene expression markers of B-cell chronic lymphocytic leukemia are present in pre-diagnostic blood samples more than 10 years prior to diagnosis

Abstract: BackgroundB-cell chronic lymphocytic leukemia (CLL) is a common type of adult leukemia. It often follows an indolent course and is preceded by monoclonal B-cell lymphocytosis, an asymptomatic condition, however it is not known what causes subjects with this condition to progress to CLL. Hence the discovery of prediagnostic markers has the potential to improve the identification of subjects likely to develop CLL and may also provide insights into the pathogenesis of the disease of potential clinical relevance.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Expanding WES panels to include the UTRs of protein-coding transcripts harboring nuORFs could extend clinical access to an expanded pool of potential neoantigens. Among the nuORFs transcribed and translated in cancer-specific manner in melanoma, GBM or CLL, were a 5' uORF in ARHGAP44, a 5' ouORF in RRAS2, and nuORFs in SOX2-OT lincRNA, each derived from a gene involved in cancer biology (Georgiadis et al 2017;Rodríguez et al 2012;Su et al 2017). Multiple additional cancer-specific nuORFs were derived from novel transcripts .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding WES panels to include the UTRs of protein-coding transcripts harboring nuORFs could extend clinical access to an expanded pool of potential neoantigens. Among the nuORFs transcribed and translated in cancer-specific manner in melanoma, GBM or CLL, were a 5' uORF in ARHGAP44, a 5' ouORF in RRAS2, and nuORFs in SOX2-OT lincRNA, each derived from a gene involved in cancer biology (Georgiadis et al 2017;Rodríguez et al 2012;Su et al 2017). Multiple additional cancer-specific nuORFs were derived from novel transcripts .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 13 nuORFs were strongly upregulated in CLL compared to GTEx and other cancer samples (Figure 4k). For example, we found a CLL-specific 5'uORF in the ARHGAP44 locus, a gene which has been shown to be upregulated in CLL patients up to 10 years prior to diagnosis (Georgiadis et al 2017). The ARHGAP44 5' uORF is translated from a 5'UTR of a CLL-specific ARHGAP44 transcript isoform, not expressed in healthy B cells and different from the isoform expressed in other tissues, such as melanoma (Figure 4l).…”
Section: Cancer-specific Nuorf Translationmentioning
confidence: 91%
“…Some such changes have already shown clinical relevance, such as BRCA1 in breast cancer, MGMT in glioblastoma multiform, and SEPT9 , which has been approved by the Food and Drug Administration (FDA) for the diagnosis of colon cancer. Since global DNA methylation is similar in resting and proliferative compartments [12], aberrant methylation patterns may be an early event in CLL, as suggested by its occurrence in blood samples collected years before diagnosis of mature B-cells neoplasm [3] and CLL [4].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant methylation patterns, which represent a molecular hallmark of cancer, are early events in tumor development, and they might represent early diagnostic biomarkers. It has been shown that methylome alterations would predict the diagnosis several years prior to the clinical appearance of the disease, thus proving to be potential markers for carrying out large-scale screening tests [3, 4]. Besides, aberrant methylation changes might represent a specific signature of different types of leukemia, depending on the originating cell [5].…”
Section: Introductionmentioning
confidence: 99%
“…Georgiadis and colleagues provided evidence that CLLlike changes at DNA methylation and transcriptome profiles existed more than 10 years before CLL diagnosis [14]. These findings suggest that the path from normal counterpart to malignant transformation and further clonal evolution is a long, multi-step process, in which DNA methylation can be viewed not only as a contributor to disease pathogenesis but also as a tool for understanding pre-malignant evolutionary trajectory.…”
Section: Dna Methylation Patterns Predict Cell Of Origin Clonal Evolmentioning
confidence: 99%